Quantification of muscle metabolites using proton magnetic resonance spectroscopy (1H-MRS) for incomplete spinal cord injury patients: preliminary study - Rusli, Nur Syahfinaz Hidayah; Zakaria, Faikah; Abdul Razak, Hairil Rashmizal (Universiti Putra Malaysia, 2021)
Introduction: This preliminary study aimed to non-invasively evaluate choline (CHO), creatine (Cr) and intramyocellular lipid (IMCL) metabolites in skeletal muscles at pre- and post-functional electrical stimulation (FES) exercise among incomplete spinal cord injury (SCI) of American Spinal Injury Association Impairment Scale (ASIA-AIS) D patients using proton magnetic resonance spectroscopy or 1 H-MRS. Methods: These metabolites were measured from the vastus lateralis and semitendinosus muscles of three incomplete SCI ASIA-AIS D patients who completed the FES exercise and later underwent 3 Tesla (T) MRI (repetition time/echo time; TR/TE of 3500ms/100ms, field-ofview; FOV of 20cm, slice thickness of 6mm) and 1 H-MRS (TR/TE of 2000ms/31ms, voxel size of 20mm x 20mm x 35mm). Results: Out of those selected metabolites, only CHO value of vastus lateralis showed a statistically significant difference between pre- and post FES exercise 1 H-MRS scanning (p = 0.01). Conclusion: Therefore, this preliminary finding has postulated that the quantification of muscle metabolites using 1 H-MRS imaging could be used as a potential indicator in evaluating the muscle strength for incomplete SCI ASIA-AIS D patients after the completion of FES cycling exercise.